How profitable climate smart agricultural practices are? Voice of farmers from rice-wheat ecologies - Rai, Munmun; Chand, Prem; Kalvaniya, Kailash C.; Jat, Hanuman Sahay; Agarwal, Tripati; Sharma, Parbodh Chander; Jat, Mangi Lal (Indian Council of Agricultural Research, 2020)
Farm record keeping can provide a look into the health of farm business, its profitability, and a snapshot in time of its present equity. However, farmers in developing country seldom maintain written records of farm operations. In many cases, farmers consider it worthless exercise. They feel overwhelmed by record keeping because it takes time, a change in behavior and for some, the requirement to learn a new skill. This study assesses the role of record keeping, particularly among women and youth using data collected in afarmers participatory research undertaken under the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). Farmers (both male and female) in climate smart villages (CSVs) of Haryana were acquainted with farm Lekha Jokha (farm budgeting) booklet designed by CIMMYT-CCAFS partners and training to fill the information was given by the field staff including male and females (CIMMYT-CCAFS 2014). The study was undertaken during 2014-15 and 2015-16. Based on the data recorded through Lekha Jokha, the study also estimated the adoption and economics of different climate smart agricultural practices (CSAPs). The farm budgeting found to be very effective tool for increased awareness among women and men farmers especially youth which lead to accelerated adoption of CSAPs. With adoption of CSAPs proven reduced climatic risk was observed in terms of yield penalty, income and distress. The results identifies a platform for social inclusive development in agriculture to promote evidence based informed policy decisions for investment prioritization.